Alpha‐blockers in the treatment of benign prostatic hypertrophy. Issue 4 (18th February 2013) - Chaplin, Steve; Kirby, Roger
Abstract: Steve Chaplin and Professor Roger Kirby provide an over ‐ view of the properties of alpha‐blockers and how they compare in the management of benign prostatic hypertrophy.